The Role of Debate Adjudication in Developing Metacognitive Listening Comprehension: A Case Study of Undergraduate EFL Students at University of Sultan Ageng Tirtayasa - Bayu Abdul Basit; Syafrizal Syafrizal; Rosmania Rima (Educational Journal, 2026)
The majority of listening lessons for English as a foreign language (EFL) students in debate-based learning environments put students in the role of debaters, rather than the adjudicator, who might be more effective in helping students acquire metacognitive listening awareness. This qualitative case study set out to do four things: (1) explain how adjudication experience helps build metacognitive listening comprehension; (2) determine how much adjudication improves monitoring and evaluating skills; (3) find out what difficulties EFL students encounter when they actually have to be the adjudicator; and (4) compare the levels of metacognitive listening awareness between new and experienced adjudicators. Participating were four undergraduates chosen using a selective selection process from the English Debate Community (EDC UNTIRTA). Stimulated Recall Tasks (SRT), semi-structured interviews, and a modified Metacognitive Awareness Listening Questionnaire (MALQ) were used to gather data, which was then analyzed using theme analysis and triangulation. The results showed that experience with adjudication activates the planning, monitoring, and evaluating parts of metacognitive listening; the most consistently developed parts among the participants were the monitoring and evaluating parts. Time constraints and fast speech rates were obstacles that had to be overcome by using tactics like contextual inference and note-taking. When compared to their less experienced peers, accredited adjudicators exhibited superior metacognitive listening habits in terms of consolidation and multidimensionality. The results of this research show that debate adjudication is a great way to help English as a foreign language students develop their metacognitive listening skills in a real-world setting.